Implementation of Law In Public Life : Challenges and Solutions for the Police Profession - Nandhini Lawrence Ananta; Edi Pranoto (Universitas Muhammadiyah Palu, 2025)
The law aims to provide fair treatment for everyone regardless of status. The law allows for fair resolution of disputes, with the existence of a judicial system, individuals can seek justice if there is a violation of their rights. In this legal role, the police profession has a strategic role in enforcing the law and maintaining order in society. The strategic role of the police is the main pillar in providing efforts to maintain order and justice in society. The police play a role in creating a safe, fair and orderly environment. The strategic role of the police is to enforce the law and ensure that the law is applied consistently and fairly. In this case, most police fail to provide justice and a sense of security to the community, and focus more on enforcing legal regulations. Therefore, it is necessary to find a solution to address these problems by improving the quality of education and training for police officers, optimizing a humanist approach in law enforcement, strengthening synergy between the police and the community, as well as digitizing and transparency of the law enforcement process.